MENGENAL BURNOUT PADA GURU - Rahman, Ulfiani (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2007)
In doing daily activities, as individual works in the public relation, sometimes faces some choices. The individual often gets conflict because of the choices. If the conflict appears but it cannot be overcome, it can arise stress. If the individual get long stress, he can be attacked by burnout syndrome. Therefore, everyone need to understand what burnout meant, what the characteristic of someone who gets burnout is, what influencing the appearance this syndrome, what aspects covering and how its psychological dynamic. The important thing explained that the individual can know earlier and avoid the syndrome attack.